Principalele teme de reformă şi dezvoltare în programele politice şi electorale din perioada tranziţiei - Fitzek, Sebastian; Stănescu, Simona Maria (Calitatea Vieții, 2017)
Within this article we proposed the analysis of main reform and development proposal of political parties involved in the government process during the transition period, in line with two directions: a. the analysis of parties behaviours in the context of multipartitism as key element of democratic games; b. an analysis of links between programs and ideological frameworks, The article includes three parts: a general description of governmental reforms and decisions adopted in the first years after the Revolution, the analysis of tendencies and systemic transformation within typologies of Romanian political parties and an assessment of reform programs of political involvement in the government process. The selection of the analysed parties was done following two dimensions: the analysis of how programs have evolved and major topics that marked the economic and political reform processes. Electoral programs of parties after December 1989 are legitimised today by the triumph of the popular speech, inefficient and not sustainable in the governance processes. In line with the theory of rational choices, decreased competition among parties, as well as the efficiency of institutional commitments should be correlate with resources used by parties and with costs and benefits of implementing certain public policies.